1998
DOI: 10.1093/bja/80.2.204
|View full text |Cite
|
Sign up to set email alerts
|

Reduced quality of clot formation with gelatin-based plasma substitutes

Abstract: SummaryWe have studied, over a wide range of dilutions using techniques of clot weight, thrombelastography and scanning electron microscopy, the physical properties of a blood clot formed in vitro when fresh blood was diluted with gelatinbased colloid solutions compared with crystalloid controls. The colloid solutions tested (3.5% polygeline (Haemaccel) and 4% succinylated gelatin (Gelofusine)) produced clots that had reduced median weight (P:0.001 and P:0.018, respectively) and reduced mean shear modulus (P:0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(58 citation statements)
references
References 13 publications
0
51
1
6
Order By: Relevance
“…We have previously shown that the determination of df is highly reproducible over the measurement range. [15] All GP data was corroborated by an experienced, blinded-assessor, independent of the study.…”
Section: Gel Point Measurements: Fractal Dimension and Clot Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that the determination of df is highly reproducible over the measurement range. [15] All GP data was corroborated by an experienced, blinded-assessor, independent of the study.…”
Section: Gel Point Measurements: Fractal Dimension and Clot Formationmentioning
confidence: 99%
“…The aim is to determine whether quantifying the changes in clot microstructure provides an improved clinical biomarker of haemostasis and clot quality, particularly in the setting of surgery, trauma and critical illness where the administration of resuscitation fluids and the associated effect on coagulation and clot quality still poses a significant clinical issue. [11][12][13][14][15] In this study the incipient clot measurements of clotting time (TGP), clot strength (GGP) and clot microstructure (df), are used to investigate the effects of progressive haemodilution by a commonly used crystalloid fluid, saline. Furthermore computational simulation was used to illustrate the relationship between clot microstructure (df) and mass incorporated into the structure during progressive dilution.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional resuscitation strategies utilize crystalloid to correct shock in order to maintain euvolemia, blood pressure, cardiac output and thus adequate oxygen delivery to Gelatin products may also cause dilution and impair fibrinogen polymerization (Mardel et al, 1998).…”
Section: Dilutional Coagulopathymentioning
confidence: 99%
“…Gelatin products can be used without the dose limitations of starch solutions, but in addition to their diluting effect fibrin polymerization is impaired 25 .…”
Section: Dilutional Coagulopathymentioning
confidence: 99%